2013
DOI: 10.2337/dc13-0316
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast Frequency and Development of Metabolic Risk

Abstract: OBJECTIVEThe relation of breakfast intake frequency to metabolic health is not well studied. The aim of this study was to examine breakfast intake frequency with incidence of metabolic conditions.RESEARCH DESIGN AND METHODSWe performed an analysis of 3,598 participants from the community-based Coronary Artery Risk Development in Young Adults (CARDIA) study who were free of diabetes in the year 7 examination when breakfast and dietary habits were assessed (1992–1993) and participated in at least one of the five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
195
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(211 citation statements)
references
References 35 publications
12
195
2
2
Order By: Relevance
“…However, this observation has not been consistent 195 across all studies (3) , with work categorising individuals by graded breakfast frequency reporting 196 no difference despite varying category definitions (2,4,21) .…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…However, this observation has not been consistent 195 across all studies (3) , with work categorising individuals by graded breakfast frequency reporting 196 no difference despite varying category definitions (2,4,21) .…”
mentioning
confidence: 85%
“…While there is a wealth of evidence for increased disease risk in those that omit 470 breakfast (1)(2)(3)(4) , randomised controlled trials that have provided causal mechanisms to explain these (total, HDL and LDL) when individuals adhered to a 1-meal a day regimen (61) . consuming breakfast daily (35) .…”
mentioning
confidence: 99%
“…The characteristics of the eight studies included are summarized in Table 1, including four prospective cohort studies (6,(15)(16)(17) , one case-control study (18) and three crosssectional studies (19)(20)(21) . These studies were published between 1998 and 2013.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The number of T2D cases ranged from sixty-one to 2423, with a total of 7419 reported T2D outcomes. With regard to study location, three studies were conducted in the USA (6,16,17) , two in China (18,20) , two in Japan (15,21) and one in Russia (19) . Six studies (15,(17)(18)(19)(20)(21) reported results for both men and women; the RR of one study (15) was available only for women; one study (6) reported results for men only; and one study (16) reported results for women only.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Breakfast eating behavior is considered a dietary pattern marker, in addition to an essential healthy lifestyle component [3,4]. Previous studies have presented evidence of associations between failure to consume breakfast and increased bodyweight [5,6], in addition to contraction of cardiovascular disease [7], metabolic conditions [8,9], dyslipidemia and insulin resistance [10], type 2 diabetes mellitus [11] and reproductive dysfunction [12]. Moreover, regular breakfast consumption has been correlated with energy balance [13], behavioral and cognitive functioning [14,15], personal wellbeing and mental health [3,16].…”
Section: Introductionmentioning
confidence: 99%